A Prospective Observational Study to Determine Perinatal Outcome of Second Twin According to Mode of Delivery in a Tertiary Care Hospital - Hetal Patel; Shelley Seth; Poulomi Roy; Chiranjit Ghosh; Shyamal Dasgupta; Pallabi Das; Shrabana Choudhuri; Jyoti Kumari; Debopriya Saha; Md Mehebub Alam (Acta Medica International)
Introduction: The mode of delivery in twin pregnancy is a challenging decision for an obstetrician as the outcome of the 2nd twin is significantly affected by that. Materials and Methods: The prospective comparative observational study was conducted for the time span of March 2021–August 2022 in a tertiary care hospital in East India. Forty-four pregnant women with twin pregnancy with gestation age >32 weeks who underwent vaginal delivery (VD) were compared with 44 pregnant with twin pregnancy who underwent cesarean section (CS). Maternal socioeconomic and obstetric parameters were noted, and the perinatal outcome of the 2nd twin was observed and compared between both elective CS and VD groups. Results: Perinatal outcome of 2nd twin through CS showed significantly better Apgar score at 1 min and at 5 min. Umbilical artery pH > 7.2 was found more in the CS group than in the VD group. Intertwin delivery interval of ≥10 min was found to be significantly associated with low Apgar score. Conclusion: The strict vigilance during follow-up of the patient in the antenatal period and proper assessment of maternal and fetal state during VD might improve the outcome of the 2nd twin to prevent unnecessary CS and its complications following it.